(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic, caused by the SARS-COV-2 virus, highlighted the need to develop safe and economically viable methods for carrying out disinfections on a commercial and domestic scale. Coronaviruses are more susceptible to UV-C radiation than fungi and bacteria and several studies related to the efficiency of UVC against the virus that causes COVID-19 have already been carried out using substitute microorganisms. Thus, this study sought to develop a device accessible to lay users for use in materials that cannot be subjected to conventional methods of eliminating microorganisms (chemical or thermal disinfection). This research proposed the production and validation of a portable UV-C emitting device for the disinfection of substrates susceptible to contamination by bacteria, fungi and pathogenic viruses. The device was developed from materials accessible to most companies and the population. Then, the device’s efficiency was validated by exposing microbial cultures (Gram positive, negative bacteria and yeast) at different time intervals. The device was developed entirely from low-cost and accessible materials. All tested microorganisms (Candida albicans, Staphylococcus aureus and Escherichia coli) were removed from the culture medium in less than 20 min. exposure. The device developed in this study can be built by most companies and the population. The device proved to be effective in reducing the risk of contagion from different pathogenic microorganisms, suggesting its effectiveness against SARS-COV-2 that causes the COVID-19 pandemic.